The effect of parental size on spermatophore production, egg quality, fertilization success, and larval characteristics in the Caribbean Spiny lobster, Panulirus argus. (17th February 2015) - Butler, Mark J.; Macdiarmid, Alison; Gnanalingam, Gaya
Abstract: The average size of spiny lobsters (Decapoda; Palinuridae) has decreased worldwide over the past few decades. Market forces coupled with minimum size limits compel fishers to target the largest individuals. Males are targeted disproportionately as a consequence of sexual dimorphism in spiny lobster size (i.e. males grow larger than females) and because of protections for ovigerous females. Therefore, overexploitation of males has led to sperm limitation in several decapod populations with serious repercussions for reproductive success. In the Caribbean spiny lobster, Panulirus argus, little is known about the effect of reduced male size on fertilization success or the role that individual size plays in gamete and larval quality. We conducted a series of laboratory experiments to test the relationship between male size and spermatophore production over multiple mating events and to determine whether spermatophore reduction and female size affected fertilization success or larval attributes in P. argus in the Florida Keys, FL (USA). We found that over consecutive matings, larger males consistently produced spermatophores of a greater weight and area than smaller males, although size-specific differences in sperm cell density were undetected and probably obscured by high variance in the data. Where spermatophores were experimentally reduced to mimic the decline in spermatophore size with declining male size, fertilization success (the number of fertilized eggs/total number of eggs extruded) declined, indicating that sperm availability is indeed limited. No maternal size effects on egg size or quality (C:N ratio) or larval quality (size, swimming speed, mortality) were observed. Our results demonstrate the importance of maintaining large males in populations of P. argus to ensure fertilization success and caution against their overexploitation through fishing, which may severely reduce reproductive success and thus population sustainability.